METHODOLOGY FOR TEACHING DIGITAL ECONOMY IN HIGHER EDUCATIONAL INSTITUTIONS OF UZBEKISTAN (Marketing Journal, 2025)
The article is devoted to the study of methodological approaches to teaching digital economy in higher educational institutions of Uzbekistan. Teaching competencies and effective pedagogical technologies that contribute to the formation of practical skills and digital literacy are considered.
Keywords: digital economy; higher education; teaching methods; pedagogical technologies; competence; blended learning; digital technologies in education